2010
DOI: 10.1002/hep.23663
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor–Like Weak Inducer of Apoptosis Is a Mitogen for Liver Progenitor Cells

Abstract: Liver progenitor cells (LPCs) represent the cell compartment facilitating hepatic regeneration during chronic injury while hepatocyte-mediated repair mechanisms are compromised. LPC proliferation is frequently observed in human chronic liver diseases such as hereditary hemochromatosis, fatty liver disease, and chronic hepatitis. In vivo studies have suggested that a tumor nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
182
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(198 citation statements)
references
References 36 publications
15
182
1
Order By: Relevance
“…Similar inhibition of ductular expansion in both KO scenarios is in keeping with the monogamous relation between this signal-receptor pair (31). Ductular expansion has previously been shown to be possible in the absence of Fn14 expression (17). Regarding the localization of macrophages to the biliary cells, previous data has described the recruitment of C-X-C chemokine receptor 4 (CXCR4 + ) cells to the biliary tracts via the chemokine Stromal Cell Derived Factor (SDF)-1 (32,33).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Similar inhibition of ductular expansion in both KO scenarios is in keeping with the monogamous relation between this signal-receptor pair (31). Ductular expansion has previously been shown to be possible in the absence of Fn14 expression (17). Regarding the localization of macrophages to the biliary cells, previous data has described the recruitment of C-X-C chemokine receptor 4 (CXCR4 + ) cells to the biliary tracts via the chemokine Stromal Cell Derived Factor (SDF)-1 (32,33).…”
Section: Discussionsupporting
confidence: 78%
“…(16). We now show that exogenous TWEAK administration results in DR expansion in vivo and in addition confirm TWEAK expression by hepatic macrophages and Fn14 expression by panCK + DRs, which have been shown to mediate ductular proliferation via NFκB activation (16,17). Herein we demonstrate a direct link between macrophage TWEAK production and paracrine signaling to recipient DRs, resulting in their expansion using complimentary TWEAK/Fn14 KO models.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Nevertheless, it appears that the TWEAK-Fn14 system is active in processes related to growth and remodeling of tissue and organs during development and tissue repair. In accordance with this, animal studies implicated the TWEAK-Fn14 system in liver progenitor cell proliferation (6,7), regulation of muscle development and muscle regeneration (8)(9)(10)(11), tumor-associated angiogenesis (12), and in various inflammationrelated pathologies including graft-versus-host disease, systemic lupus erythematosus-related nephritis (13), 2,4,6-trinitrobenzene sulfonic acid-induced colitis (14), renal and cerebral ischemia (15)(16)(17)(18), and collagen-induced arthritis (19,20).…”
mentioning
confidence: 67%
“…Previous studies revealed, that Fn14 is also overexpressed in poorly differentiated HCC cell lines (Feng et al, 2000) and the TWEAK/Fn14 pathway promoted the proliferation of multiple HCC cell lines in vitro (Kawakita et al, 2005). A recent investigation demonstrated, that the TWEAK/ Fn14 pathway can stimulate liver progenitor cell (LPC) mitosis in the rapid growth phase during response to choline-deficient, ethionine-supplemented (CDE) dietinduced injury and re-generation in vivo (Tirnitz-Parker et al, 2010). Nonetheless, the prognostic value of Fn14 for HCC has yet to be explored and this study evaluates the clinical significance of Fn14 in HCC patients after curative resection.…”
Section: Introductionmentioning
confidence: 99%